The effect of feldenkrais exercise on reducing lower back pain in elderly social services of banten province - Annisa Putri Fahmawati; Junaidi Junaidi; Nadya Dwi Oktafiranda; Ela Yuliana; Sandi Prayudho (Universitas Riau, 2024)
(English)This study aims to determine the effect of Feldenkrais Exercise to reduce pain in elderly people suffering from low back pain at the Banten Provincial Social Service Home. The research method used is pre-experimental method with Pre and Post Test with One Group Design. By comparing two evaluation results, namely pre-test and post-test. In this study, the instrument used was Numerical Rating Scales (NRS) which is used to assess pain intensity using numbers 1-10. The population in this study were elderly people at the Banten Provincial Social Service Home totaling 54 people, the sample in this study amounted to 10 people, using purposive sampling technique that met the inclusion criteria. With the data analysis technique in this study using the Wilcoxon Test (paired sample test) which is a non-parametric test. Based on the results of hypothesis testing, it is found that the hypothesis is accepted, namely Feldenkrais exercise has an effect on reducing low back pain in the elderly at the Banten Provincial Social Service Home where the average value of positive rank = 0.00 and negative rank = 5.50, so there is a decrease in low back pain in the elderly. Based on the results of the research that has been described, it can be concluded that there is a decrease in low back pain as evidenced by the data results with a value of 0.004 <0.05, so there is a significant difference. This concludes that Feldenkrais exercise can be used as an exercise program that is easy for the elderly to do in reducing low back pain.(Indonesian)Penelitian ini bertujuan untuk mengetahui pengaruh Feldenkrais Exercise untuk menurunkan nyeri pada lansia yang menderita nyeri punggung bawah di Panti Dinas Sosial Provinsi Banten. Metode penelitian yang digunakan adalah metode pre-experimental dengan rancangan Pre and Post Test with One Grup Design. Dengan membandingkan dua hasil evaluasi yaitu pre-test dan post-test. Pada penelitian ini instrument yang digunakan adalah Numerical Rating Scales (NRS) yang digunakan untuk menilai intensitas nyeri dengan menggunakan angka 1-10. Populasi dalam penelitian ini adalah lansia di Panti Dinas Sosial Provinsi Banten sejumlah 54 orang, sampel dalam penelitian ini berjumlah 10 orang, dengan menggunakan teknik purposive sampling yang memenuhi syarat kriteria inklusi. Dengan Teknik analisis data dalam penelitian ini menggunakan Uji Wilcoxon (Uji sampel berpasangan) yang merupakan uji non-parametrik. Berdasarkan Hasil uji hipotesis diperoleh bahwa hipotesis diterima, yaitu feldenkrais exercise berpengaruh terhadap penurunan nyeri punggung bawah pada lansia di Panti Dinas Sosial Provinsi Banten dimana diperoleh nilai rerata positive rank = 0,00 dan negative rank = 5,50, maka terjadi penurunan nyeri punggung bawah pada lansia. Berdasarkan hasil penelitian yang telah diuraikan dapat ditarik kesimpulan bahwa terdapat penurunan nyeri punggung bawah dibuktikan juga dengan hasil data dengan nilai sebesar 0,004 < 0,05 maka terdapat perbedaan yang signifikan. Hal ini menyimpulkan bahwa feldenkrais exercise dapat dijadikan program latihan yang mudah dilakukan oleh lansia dalam menurunkan nyeri punggung bawah. Copyright © The Author (s) 2024Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.